Antimicrobial and anti-inflammatory properties of various seaweeds from the Gulf of Thailand - Boonchum W. (2014)
Aqueous (AE) and ethanolic extracts (EE) from four species of seaweed: Sargassum binderi Sonder, Amphiroa sp., Turbinaria conoides (J. Agardh) Küzting and Halimeda macroloba Decaisne from the east cost of the Gulf of Thailand were screened for antibacterial and antifungal activities. The test organisms were Staphylococcus aureus, S. epidermidis, Propionibacterium acnes, Proteus mirabilis and Candida albicans. Extracts of all the species were found to have antimicrobial activities. AE of T. conoides, however demonstrated the maximum efficacy. Therefore, AE of T. conoides was also evaluated for its anti-inflammatory effect using EPP-induced ear edema and carrageenin-induced hind paw edema tests. Results revealed anti-inflammatory activity of AE of T. conoides comparable to that phenylebutazol and acetylsalicylic acid used as standard controls. Irritation test indicated that AE of T. conoides is also safe to be used in cosmeceutical or pharmaceutical products for skin as an antibacterial and antifungal agent against the organisms considered in this study. © 2011 Friends Science Publishers.